2021
DOI: 10.47895/amp.vi0.1753
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Stroke and its Risk Factors in the Philippines: A Systematic Review

Abstract: Background. Various epidemiologic studies reported different stroke incidence and prevalence rates in the Philippines. Thus, there is a need to synthesize existing information on these indicators to depict more accurate evidence on the burden on stroke in the country.Objective. The objective of this systematic review is to provide evidence on the incidence and prevalence of stroke in the Philippines, as well as its associated risk factors.Methods. PubMed and HERDIN were searched for available full-text Philipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…While community health center stroke symptom awareness is an integral part of the proposed program, we acknowledge that attendance to this alone may not be sufficient to make an overall substantial impact on stroke prevention. A recent systematic review revealed that hypertension is still the frequently cited risk factor for stroke, along with diabetes, smoking, and elevated levels of cholesterol (9). Furthermore, in a large prospective cohort study of 155,722 individuals, approximately 70% of cardiovascular disease (defined as myocardial infarction, stroke and heart failure) cases, were found to be associated with modifiable risk factors (10).…”
Section: Community-based Stroke Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…While community health center stroke symptom awareness is an integral part of the proposed program, we acknowledge that attendance to this alone may not be sufficient to make an overall substantial impact on stroke prevention. A recent systematic review revealed that hypertension is still the frequently cited risk factor for stroke, along with diabetes, smoking, and elevated levels of cholesterol (9). Furthermore, in a large prospective cohort study of 155,722 individuals, approximately 70% of cardiovascular disease (defined as myocardial infarction, stroke and heart failure) cases, were found to be associated with modifiable risk factors (10).…”
Section: Community-based Stroke Preventionmentioning
confidence: 99%
“…Despite not having a unified national registry for stroke cases, the national stroke incidence rate ranged from 3.95 to 5.61%. [9] Under the framework of the building blocks of the health system by the WHO, an extensive review article by Collantes et al highlighted the several gaps in stroke care in the Philippines (11). Among these is targeted improving patient awareness of stroke symptoms along with prompt emergency medical services (EMS) dispatch.…”
Section: Decentralized Targeted Stroke Awarenessmentioning
confidence: 99%
“…1 It is a disease with a high public health and financial burden, particularly in lowincome countries. [2][3][4] At present, the only proven treatments to recover brain tissue at risk in acute ischemic stroke are intravenous thrombolysis with recombinant tissue plasminogen activator (rTPA, or alteplase) within 4.5 hours of ischemic stroke onset 5,6 , and more recently endovascular thrombectomy up to 24 hours. 7,8 Beyond these time windows, only medication for secondary stroke prevention can be given.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, access to these essential treatments may be limited especially in low-income countries due to social barriers to healthcare. 2,3 It is therefore beneficial to study other promising and easily accessible strategies to improve stroke recovery such as neuroprotective agents.…”
Section: Introductionmentioning
confidence: 99%